Fragility Assesment of Mid-Rise RC Building using HAZUS Method in High Seismic Zone - Zuher, M. Hasbi; Nasution, Ade Prayoga; Sidiq, Zairah Nabila; Masrilayanti, Masrilayanti; Tanjung, Jafril (Jurnal Bangunan, Konstruksi & Desain, 2023)
Earthquake is a pounding that caused by a released energy of ground motion. The earthquake in high seismic zone caused damages and loss of live. Thus, there was important to evaluate the seismic vulnerability of structure before an earthquake was occurred to prevent the damage and safe of lives. The seismic vulnerability can be described by using fragility curves. These fragility curves was developed by HAZUS method that present the probability of the structure damage due to various ground shaking or lateral displacement of the building. This paper addresses the performance based design method to consider the building capacity due to Padang ground motion. Therefore, the damage probability was calculated by using the lognormal distribution with the probabilistic parameter was acquired by HAZUS engineering building module. Then, the fragility assesment of the building was compared in transverse and longitudinal direction. The result reveals that the building is vulnerable to collapse due to Padang ground motion.